Why We Fight: The Origins, Nature, and Management of Human Conflict - Churchman, David (Hamilton Books, 2013)
This book draws on twenty-four academic disciplines to provide a critical analysis of some 100 theories that explain the origins, nature, and management of human conflict. The book treats intellectual, individual, moral, interpersonal, organizational, community, political, and international conflicts. It suggests six criteria for distinguishing good from bad theory and discusses how existing theories may be used and improved.